Association of Copper Status with Lipid Profile and Functional Status in Patients with Amyotrophic Lateral Sclerosis - Acsa Nara A. B. Barros; Mário Emílio T. Dourado; Lucia de Fatima C. Pedrosa; Lucia Leite-Lais (Journal of Nutrition and Metabolism)
Oxidative stress is one of the main mechanisms associated with the pathogenesis of amyotrophic lateral sclerosis (ALS). Copper can affect cellular oxidation and lipid metabolism. The aim of this study was to evaluate the association of copper status with lipid profile and functional status in patients with ALS. A cross-sectional study was carried out including 27 patients with ALS (case group) and 26 healthy individuals (control group). Copper status was evaluated by habitual dietary copper intake, plasma copper, and serum ceruloplasmin concentrations. The lipid profile included analysis of serum total cholesterol (TC), LDL-cholesterol (LDL-c), HDL-cholesterol (HDL-c), and triglycerides (TGL). The functional status of patients with ALS was assessed by the ALS Functional Rating Scale-Revised (ALSFRS-R). In the case group, plasma copper was lower compared with the control group (133.9 versus 164.1 μg/dL, p=0.0001) and was positively correlated with HDL-c (rs=0.398, p=0.044). In the control group, plasma copper was positively correlated with serum ceruloplasmin (rs=0.646, p<0.001), TC (rs=0.446, p=0.025), LDL-c (rs=0.445, p=0.029), and HDL-c (rs=0.479, p=0.015), and serum ceruloplasmin was positively correlated only with LDL-c (rs=0.407, p=0.043). In the case group, dietary copper intake (B=−0.373, p<0.001), plasma copper (B=−0.005, p=0.033), and TC (B=−0.312, p=0.001) were inversely associated with the functional status of patients with ALS. In contrast, serum ceruloplasmin (B=0.016, p=0.044), LDL-c (B=0.314, p=0.001), HDL-c (B=0.308, p=0.001), and TGL (B=0.062; p=0.001) were positively associated with their functional status. In conclusion, this study suggests a disturbance of copper status and its connection with the lipid profile in patients with ALS. Furthermore, copper status and lipid profile may influence the functional status of patients with ALS, standing out as potential biomarkers of disease severity.